Handling Children Who Commit Crimes Under the Criminal Justice System - Hadi Tuasikal; Asmuruf, Johana (Journal of Law Justice (JLJ), 2024)
The purpose of this study is to find out how the handling of criminal acts committed by minors based on the juvenile justice system. Using normative legal research methods, it is concluded: 1. In the Criminal Code, there are two kinds of elements, namely objective elements and subjective elements. The objective element is the element related to the situation, which is the state in which the actions of the perpetrator must be carried out, while the subjective element is the element inherent in the perpetrator or related to the perpetrator. The subjective element of a criminal act is intentional or accidental (dolus or culpa); purpose or intention on an experiment or poging as referred to in Article 53 paragraph 1 of the Criminal Code. The objective element of a criminal act is the unlawful nature or wederrechtelijkheid; the quality of the perpetrator, for example "the state of being a public servant" in a crime of office according to Article 415 of the Criminal Code or "the state of being an administrator or commissioner of a limited liability company" in a crime according to Article 398 of the Criminal Code; and causality, which is the relationship between an action as a cause and a reality as an effect. 2. Every minor who commits the crime of murder has different legal sanctions than adults who commit murder. Article 3 letter f of Law Number 11 of 2012 states that every child in the criminal justice process has the right not to be sentenced to death or life imprisonment, only subject to diversion efforts aimed at achieving peace between victims and children, resolving cases outside the judicial process, preventing children from being deprived of independence, encouraging the community to participate and instilling a sense of responsibility to children,  and job training in prisons for minors.